PENINGKATAN PRODUKSI DAN PEMASARAN UKM BANDENG PRESTO DI SEMARANG - Anis, Samsudin; Agustina, Titin (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2017)
The purpose of science and technology activities for the community is to solve the problems  faced  by  IbM  partners  covering  aspects  of  production,  quality  and  hygiene,  busi- ness  management,  and  product  marketing.  There  are  two  partners  of  SMEs  who  are  engaged in processing and marketing of milkfish presto in Semarang. To achieve the targets of activities  carried  out  by  various  methods  tailored  to  the  purpose  of  activities,  such  as  lectures / counseling, demonstrations, direct practice, and mentoring. The results of IbM activities are: 1) Produced a unit of presto fuel-saving fuels maker with a production capacity of at least 30 kg once cook 2) Produced one unit of oven milkfish presto tool that has been cooked;3)  Known  the  nutritional  value  of  milkfish  presto  (proximate  test),  among  others  protein,  fat,  carbohydrate,  calcium,  water  content,  and  abui  level;  4)  Produce  a  typical  presto milkfish recipe production Part I or Partner II that can be widely accepted by consumers; 5)  Produce  the  design  and  quality  of  presto  milk  packaging  more  interesting;  6)  Produced P-IRT  permit  from  Dinas  Kesehatan  for  Partners  II;  7)  The  pattern  of  business  management  (bookkeeping,  promotion,  marketing)  of  presto  milkfish  industry  is  neat  and  modern